HUBUNGAN GAYA BELAJAR VISUAL DENGAN NUMBER SENSE PADA SISWA SEKOLAH DASAR DI KOTA BUKITTINGGI - Nora Pramita; Duryati Duryati (Universitas Negeri Padang, 2020)
The relationship between visual learning style and number sense in elementary school students in Bukittinggi city. This study aims to determine the relationship between visual learning styles with number sense in elementary school students in the city of Bukittinggi. This type of research is quantitative research methods, namely correlational. The subjects in this study were fifth grade elementary school students in the city of Bukittinggi, amounting to 97 people using cluster sampling techniques. The results of this study indicate the value of the correlation coefficient (r) = -0.023 ˂ 0.195 or seen from the value of p = 0.821> 0.05 which means Ha is rejected and Ho is accepted. The conclusion of this study is that there is no relationship between visual learning styles with number sense in elementary school students in the city of Bukittinggi. In addition, fifth grade elementary school students in Bukittinggi City have a visual learning style with a high category and number sense abilities with a medium category.Hubungan gaya belajar visual dengan number sense pada siswa sekolah dasar di Kota Bukittinggi. Penelitian ini bertujuan untuk mengetahui hubungan antara gaya belajar visual dengan number sense pada siswa sekolah dasar di Kota Bukittinggi. Jenis penelitian ini adalah kuantitatif dengan metode penelitian, yaitu korelasional. Subjek dalam penelitian ini adalah siswa kelas lima sekolah dasar di Kota Bukittinggi yang berjumlah 97 orang dengan menggunakan teknik cluster sampling. Hasil penelitian ini menunjukkan nilai koefisien korelasi (r) = -0,023 ˂ 0,195 atau dilihat dari nilai p = 0,821 > 0,05 yang berarti Ha ditolak dan Ho diterima. Kesimpulan dari penelitian ini adalah tidak terdapat hubungan antara gaya belajar visual dengan number sense pada siswa sekolah dasar di Kota Bukittinggi. Selain itu, siswa kelas lima sekolah dasar di Kota Bukittinggi mempunyai gaya belajar visual dengan kategori tinggi dan kemampuan number sense dengan kategori sedang.